Advances in environmental remote sensing : sensors, algorithms, and applications - Weng, Qihao (Boca Raton : CRC Press, 2011)
"Featuring contributors from 17 countries, this book systematically presents recent advances in environmental remote sensing. First, the text provides the latest developments in remote sensing data and sensor systems, paying special attention to LIDAR, hi
Includes bibliographical references and index. section 1. Sensors, systems, and platforms -- section 2. Algorithms and techniques -- section 3. Environmental applications-vegetation -- section 4. Environmental applications : air, water, and land. Also ava
Keywords: Environmental sciences -- Remote sensing; Çevre bilimleri -- Uzaktan algılama